Effect of Iron Deficiency on Thyroid Hormone Function and Haematological Parameters in Malnourished Children. - Ur Rashid, Haroon; Saleem, Shafaq; Hassan, Javaid; Haroon, Mohammad; Amin, Bubrak; Ahmed, Irshad (Journal of Neonatal Surgery, 2025)
Background: Malnutrition and iron deficiency are significant health issues in the developing world, which can result in a number of physiological dysfunctions. Recent studies have shown that iron is essential for thyroid hormone production and that iron deficiency may lead to thyroid dysfunction, especially in at-risk children. Objective: To evaluate the effect of iron deficiency on thyroid hormone function and hematological parameters in malnourished children. Methods: This cross-sectional, analytical study took place at Kabir Medical College between January 2024 and January 2025. Consecutive sampling of 72 malnourished children (1-10 years) was done. Hematological indices, iron indices (serum iron, TIBC, ferritin) and thyroid indices (TSH, FT3, FT4) were measured. SPSS version 25 was used for statistical analysis. Independent t-test, Pearson correlation and chi-square test were used and p ≤ 0.05 was taken as significant. Results: Iron deficiency was observed in 61.1% of children. Thyroid dysfunction was identified in 33.3% of cases, with subclinical hypothyroidism being the most common. Iron-deficient children had significantly higher TSH and lower FT3 and FT4 levels compared to non-deficient children (p < 0.001). A strong negative correlation was found between serum ferritin and TSH (r = -0.61, p < 0.001), while positive correlations were observed with FT3 and FT4. Severe malnutrition was significantly associated with thyroid dysfunction (p = 0.002). Conclusion: Iron deficiency significantly affects thyroid hormone function and hematological parameters in malnourished children. Early identification and management of iron deficiency may help prevent thyroid dysfunction and improve overall health outcomes in this population.. ..